Specificity of Modern TV Report Variety (Proceedings of Southern Federal University. Philology, 2019)
Sergey V. Karpiy (Donetsk National University. Donetsk, DPR)Considering the fact that television as a means of mass communication is still one of the key tools for quickly informing the audience about socially significant events in the country and the world, it is important to accurately define and understand the arsenal of tools that this type of media has. This is especially true for news services, where journalists regularly use such an operational genre as a television report. During the entire period of its evolution and technical progress, it acquired new types that are characterized by their own specificity of application, construction, implementation on the television screen. Because of their similarity, the substitution of concepts and their incorrect interpretation take place. In order to eliminate this factor, it is necessary to clearly identify modern types of TV coverage, as well as specifically identify their common and distinctive features. In this article, such concepts as “uncommented report”, “commented report”, “live report” are considered in more detail, parallels are drawn between them, the difference and specificity of architectonics are revealed.Key words: report, live broadcast, uncommented report, live report, television, television journalism, air, broadcast, broadcast.DOI 10.23683/1995-0640-2019-3-225-229 Sergey V. Karpiy (Donetsk National University. Donetsk, DPR)Considering the fact that television as a means of mass communication is still one of the key tools for quickly informing the audience about socially significant events in the country and the world, it is important to accurately define and understand the arsenal of tools that this type of media has. This is especially true for news services, where journalists regularly use such an operational genre as a television report. During the entire period of its evolution and technical progress, it acquired new types that are characterized by their own specificity of application, construction, implementation on the television screen. Because of their similarity, the substitution of concepts and their incorrect interpretation take place. In order to eliminate this factor, it is necessary to clearly identify modern types of TV coverage, as well as specifically identify their common and distinctive features. In this article, such concepts as “uncommented report”, “commented report”, “live report” are considered in more detail, parallels are drawn between them, the difference and specificity of architectonics are revealed.Key words: report, live broadcast, uncommented report, live report, television, television journalism, air, broadcast, broadcast.